2021
DOI: 10.5751/es-12080-260122
|View full text |Cite
|
Sign up to set email alerts
|

Systematic learning in water governance: insights from five local adaptive management projects for water quality innovation

Abstract: Adaptive management has been proliferating since the 1970s as a policy approach for dealing with uncertainty in environmental governance through learning. Learning takes place through a cyclical approach of experimentation and (possible) adjustment. However, few empirical studies exist that cover full iterations of adaptive management cycles. We report on five adaptive management projects on water quality enhancement, of which four led to innovations in the small-scale management of waterways in northern Germa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
0
2
0
1
Order By: Relevance
“…Aunque la gestión adaptativa está ampliamente considerada como un enfoque efectivo para gestionar la incertidumbre a través del aprendizaje con el fin de conservar, gestionar y restaurar los ecosistemas y las poblaciones de especies 297 , su implementación satisfactoria se ve limitada por la falta de mecanismos de seguimiento efectivos 298 , desafíos para hacer frente a la incertidumbre y la falta de mecanismos institucionales adecuados para su implementación, entre otros problemas 299,300,301,302 . En consecuencia, el enfoque de gobernanza adaptativa se entiende cada vez más como un mecanismo más amplio y prometedor para abordar los requisitos sociales e institucionales de la gestión adaptativa y, al mismo tiempo, facilitar la transformación socioecológica 300,303 . Sin embargo, el enfoque de la gobernanza adaptativa también tiene sus propios desafíos conceptuales y de implementación que deben abordarse para mejorar su éxito, dada la insuficiencia de evidencia sobre su implementación efectiva 298 y dudas sobre su capacidad para provocar cambios transformadores 304 .…”
Section: Gestión Adaptativaunclassified
“…Aunque la gestión adaptativa está ampliamente considerada como un enfoque efectivo para gestionar la incertidumbre a través del aprendizaje con el fin de conservar, gestionar y restaurar los ecosistemas y las poblaciones de especies 297 , su implementación satisfactoria se ve limitada por la falta de mecanismos de seguimiento efectivos 298 , desafíos para hacer frente a la incertidumbre y la falta de mecanismos institucionales adecuados para su implementación, entre otros problemas 299,300,301,302 . En consecuencia, el enfoque de gobernanza adaptativa se entiende cada vez más como un mecanismo más amplio y prometedor para abordar los requisitos sociales e institucionales de la gestión adaptativa y, al mismo tiempo, facilitar la transformación socioecológica 300,303 . Sin embargo, el enfoque de la gobernanza adaptativa también tiene sus propios desafíos conceptuales y de implementación que deben abordarse para mejorar su éxito, dada la insuficiencia de evidencia sobre su implementación efectiva 298 y dudas sobre su capacidad para provocar cambios transformadores 304 .…”
Section: Gestión Adaptativaunclassified
“…In water governance, especially under the uncertainty of climate change impact, AM involves transforming the way water managers view problems and act, focusing on the learning process as a crucial element for promoting adaptive capacity while embracing uncertainty (Kochskämper et al, 2021). The IPCC defines adaptive capacity (AC) as 'the ability of systems, institutions, humans, and other organisms to adjust to potential damage, to take advantage of opportunities or to respond' (IPCC, 2014, p. 118).…”
Section: Ways Of Knowing Adaptive Management and Building Adaptive Capacitymentioning
confidence: 99%
“…Research on organizational learning has found that early failures provide better learning opportunities than failures that come later (Khanna et al, 2016). The fail-fast approach shares a focus on learning and adaptation with adaptive management (Walters & Holling, 1990), which has gained widespread acceptance in the conservation field (Kochskämper et al, 2021). The fail-fast approach may be best viewed as a re-framing of adaptive management with greater emphasis on failure and on rapid testing and evaluation.…”
Section: Introductionmentioning
confidence: 99%